2005
DOI: 10.1515/jpm.2005.077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of open vs. closed system endotracheal suctioning on cerebral blood flow velocities in mechanically ventilated extremely low birth weight infants

Abstract: The mode of suctioning or ventilation does not influence CBFVs in ELBW infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…1,5,14,16 Furthermore, all but 7% of VLBW infants had increases in mean CBFv following suctioning (without preceding decreases), which is consistent with observations by Perlman et al 1 Others using near infrared spectroscopy also observed brief increases in cerebral blood volume after tracheal suctioning. 4,11 In this study, we observed that mean CBFv peaked at 6 min and remained elevated for approximately 25 min after suctioning.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…1,5,14,16 Furthermore, all but 7% of VLBW infants had increases in mean CBFv following suctioning (without preceding decreases), which is consistent with observations by Perlman et al 1 Others using near infrared spectroscopy also observed brief increases in cerebral blood volume after tracheal suctioning. 4,11 In this study, we observed that mean CBFv peaked at 6 min and remained elevated for approximately 25 min after suctioning.…”
Section: Discussionsupporting
confidence: 87%
“…While some investigators observed that CBF changes returned to baseline within 1 to 2 min after suctioning, 1,4,9 most did not report the duration of CBF disturbances. 5,10,14,16 Moreover, while the large difference in duration of CBF changes noted by us and others may be due to differences in population characteristics, inclusion of small sample sizes, different suctioning techniques, use of pre-oxygenation or sedation policies, and so on, we believe that the main difference and strength of our study is that we examined infants who clinically required suctioning and used continuous monitoring until disturbed physiological variables returned to baseline.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations